2015
DOI: 10.15585/mmwr.mm6435a4
|View full text |Cite
|
Sign up to set email alerts
|

Injuries and Traumatic Psychological Exposures Associated with the South Napa Earthquake — California, 2014

Abstract: On August 24, 2014, at 3:20 a.m., a magnitude 6.0 earthquake struck California, with its epicenter in Napa County (1). The earthquake was the largest to affect the San Francisco Bay area in 25 years and caused significant damage in Napa and Solano counties, including widespread power outages, five residential fires, and damage to roadways, waterlines, and 1,600 buildings (2). Two deaths resulted (2). On August 25, Napa County Public Health asked the California Department of Public Health (CDPH) for assistance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
4
1
Order By: Relevance
“…Although the previous studies indicate that past traumatic experiences increase trauma response level (4,14,44,45), this study did not support this outcome. In our study, neither being nor not being traumatized before did not show an effect on the level of trauma, except for previous earthquake experiences.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Although the previous studies indicate that past traumatic experiences increase trauma response level (4,14,44,45), this study did not support this outcome. In our study, neither being nor not being traumatized before did not show an effect on the level of trauma, except for previous earthquake experiences.…”
Section: Discussioncontrasting
confidence: 99%
“…The probability of developing PTSD after an earthquake is related to the magnitude of the earthquake, preparedness, location during the earthquake, injuries or near-death experiences, dead or missing family members, material losses, reactions to the trauma (dissociation, coping and other reactions), work-related stress factors (lack of communication, heavy workload, etc.) and posttraumatic factors (symptoms, social support and other daily-life sources of stress) (13,14). However, exposure to disaster trauma might not be enough on its own to explain how individuals develop PTSD.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, about 30% of the population suffered from post-traumatic stress disorder. 39 In China, a study of schoolchildren reported that about 40% of the students had post-traumatic stress disorder. 40 In Haiti, post-traumatic stress disorder prevalence in school-aged children was 50%.…”
Section: Permanent Health Effects (Mental Health Disability Poverty)mentioning
confidence: 99%
“…, 38 After the South Napa Earthquake in California, the majority of households (50-75%) reported that one or more household members had experienced anxiety, fear, or distraction during or since the earthquake. Similarly, about 30% of the population suffered from post-traumatic stress disorder 39 . In China, a study of schoolchildren reported that about 40% of the students had post-traumatic stress disorder 40 .…”
Section: Permanent Health Effects (Mental Health Disability Poverty)mentioning
confidence: 99%
“…Surveys in New York City, for example, showed that substantial numbers not directly affected by the attack exhibiting similar PTSD symptoms (Galea et al 2003). Additional research on the aftermath of earthquakes confirm the widespread effect of psychosocial trauma on diverse groups in and outside the disaster area (Livanou et al 2002;Attfield et al 2015). Other studies point out that such surges are particularly prevalent in cases of chemical, biological or radiation type disasters especially toxic spills (Svendsen et al 2012), various environmental hazards and most recently the Corona Virus pandemic (Villa 2020); all the consequence of an initial disaster (Stellman et al 2008).…”
Section: Introductionmentioning
confidence: 91%